Blinding in randomised clinical trials of psychological interventions: a retrospective study of published trial reports. Issue 3 (30th September 2020) - Juul, Sophie; Gluud, Christian; Simonsen, Sebastian; Frandsen, Frederik Weischer; Kirsch, Irving; Jakobsen, Janus Christian
Abstract : Objectives: To study the extent of blinding in randomised clinical trials of psychological interventions and the interpretative considerations if randomised clinical trials are not blinded. Design: Retrospective study of trial reports published in six high impact factor journals within the field of psychiatry in 2017 and 2018. Setting: Trial reports published in World Psychiatry, JAMA Psychiatry, Lancet Psychiatry, American Journal of Psychiatry, British Journal of Psychiatry, or Psychotherapy and Psychosomatics . Main outcome measures: Blinding status of participants, treatment providers, outcome assessors, data managers, the data safety and monitoring committee, statisticians and conclusion makers, if trialists rejected the null hypothesis on the primary outcome measure, and if trialists discussed the potential bias risk from lack of blinding in the published trial report. Results: 63 randomised clinical trials of psychological interventions were identified. None (0%; 95% CI 0% to 5.75%) of the trials reported blinding of all possible key persons. 37 (58.7%; 95% CI 46.42% to 70.04%) trials reported blinding of outcome assessors. Two (3.2%; 95% CI 0.87% to 10.86%) trials reported blinding of participants. Two (3.2%; 95% CI 0.87% to 10.86%) trials reported blinding of data managers. Three (4.8%; 95% CI 1.63% to 13.09%) trials reported blinding of statisticians. None of the trials reported blinding of treatment providers, the data safety and monitoring committee, and conclusion makers. 45 (71.4%; 95% CI 59.30% to 81.10%) trials rejected the null hypothesis on the primary outcome(s). 13 (20.7%; 95% CI 12.48% to 32.17%) trials discussed the potential bias risk from lack of blinding in the published trial report. Conclusions: Blinding of key persons involved in randomised clinical trials of psychological interventions is rarely sufficiently documented. The possible interpretative limitations are only rarely considered. There is a need of randomised clinical trials of psychological interventions with documented blinding attempts of all possible key persons.